The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/21582440221129105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the University’s Environment and Support System on Subjective Social Norms as Precursor of the Entrepreneurial Intention of Students

Abstract: In this study, we aim to understand the influence of the university’s environment and support system (ESS) on subjective social norms (SSN) as one of the precursors of the entrepreneurial intention (EI) of university students. For this, we applied a customized mathematical model of EI based on the theory of planned behavior to probe whether the university’s ESS can affect SSN and analyze the paths that this influence may follow to form the EI of students. In other words, this study argues that the university p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…Hence the study proposed analyzing the relationship between prior business experience and entrepreneurial education. Additionally, individuals develop a strong attitude toward entrepreneurial intentions with the help of entrepreneurial education ( Bazan et al, 2019 ), as education is one of the strong motivators for an entrepreneurship career ( Urbano et al, 2020 ). Likewise, education is also an outcome of a significantly planned behavior because individuals intend a suitable education, apply for it, and get (receive) their desired education.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Hence the study proposed analyzing the relationship between prior business experience and entrepreneurial education. Additionally, individuals develop a strong attitude toward entrepreneurial intentions with the help of entrepreneurial education ( Bazan et al, 2019 ), as education is one of the strong motivators for an entrepreneurship career ( Urbano et al, 2020 ). Likewise, education is also an outcome of a significantly planned behavior because individuals intend a suitable education, apply for it, and get (receive) their desired education.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…(Giacomin et al,2011), A survey among university students was carried out revealed that male students show more positive attitudes toward entrepreneurship and much more concrete entrepreneurial intentions. And Furthermore, studies have affirmed this relationship empirically that more excellent entrepreneurial attitude positively enhances one's entrepreneurial intention drive (Anwar et al, 2020;Anwar & Saleem, 2018;Bazan et al, 2019;Krueger et al, 2000;Autio et al, 1997;Pruett et al, 2009;Segal et al, 2005;Van Gelderen & Jansen, 2008).Existing; research findings show that personal characteristics are important factors that influence attitudes towards entrepreneurship (Baron & Markman, 2003;Baum & Locke, 2004;Collins et al, 2004).…”
Section: Entrepreneurial Intentionmentioning
confidence: 95%
“…“I never thought about it [entrepreneurship],” explained one participant. Rather, participation in university programs catalyzed entrepreneurial intention, which several participants described as “catching the bug.” This finding suggests that entrepreneurism is something that can be encouraged through academic programs and public policy (Bazan et al 2019; O'Brien and Cooney 2019; Bramwell 2020). It also confirms that entrepreneurism is not limited to international newcomers who arrive through designated immigrant entrepreneur programs (Graham and Pottie‐Sherman 2021).…”
Section: Findings: International Student Entrepreneurs and The Entrep...mentioning
confidence: 98%
“…No longer simply research and teaching institutions, universities are now expected to enable entrepreneurship and commercialize academic research (O'Brien and Cooney 2019). Within this context, actors within the triad of government, university, and industry increasingly see students as potential inventors whose entrepreneurial intentions can be sparked through entrepreneurship education, cultivated through Technology Transfer Offices (TTOs) and on‐campus incubators (Etzkowitz and Zhou 2017; Sandström et al 2018; Bazan et al 2019; Nicholls‐Nixon et al 2020).…”
Section: International Student Mobility and The University As A Globa...mentioning
confidence: 99%